Autophagy genes in biology and disease - Yamamoto, Hayashi; Zhang, Sidi; Mizushima, Noboru (Nature reviews. Genetics, 2023)
Macroautophagy and microautophagy are highly conserved eukaryotic cellular processes that degrade cytoplasmic material in lysosomes. Both pathways involve characteristic membrane dynamics regulated by autophagy-related proteins and other molecules, some of which are shared between the two pathways. Over the past few years, the application of new technologies, such as cryo-electron microscopy, coevolution-based structural prediction and in vitro reconstitution, has revealed the functions of individual autophagy gene products, especially in autophagy induction, membrane reorganization and cargo recognition. Concomitantly, mutations in autophagy genes have been linked to human disorders, particularly neurodegenerative diseases, emphasizing the potential pathogenic implications of autophagy defects. Accumulating genome data have also illuminated the evolution of autophagy genes within eukaryotes as well as their transition from possible ancestral elements in prokaryotes.